(untitled) - Lurie, Karen (New York, 2006)
Cracking the GRE brings you proven techniques from the test prep experts! The 2007 edition includes over 300 practice questions and exclusive free access to practice exams and further review online. In Cracking the GRE, we’ll teach you how to think like the test writers and Solve analogies even when you don’t know the meanings of all the words in the problem. Crack even the most complex algebra problems by plugging in numbers in place of variables. Understand the nature of computer-adaptive tests and use that knowledge to your advantage. Master even the toughest problems in the Verbal and Quantitative sections
Keywords: Tiếng Anh,English language; Sách giáo khoa cho người nước ngoài,Textbooks for foreign speakers